2003
DOI: 10.5713/ajas.2003.1011
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Oxygen Uptake by Yeast Issatchenkia orientalis as Microbial Feed Additive for Ruminants

Abstract: The objective of this work was to evaluate a thermotolerant yeast Issatchenkia orientalis DY252 as a microbial feed additive for ruminants. In the present study, the influence of volatile fatty acids (VFA) and temperature on oxygen uptake rate by I. orientalis DY 252 was investigated. It was evident that the oxygen uptake rate was decreased gradually as the VFA concentrations increased in a range of 30 to 120 mM. Although the oxygen uptake rate was not greatly affected by temperature in the range 37 to 43°C, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…Effective degradability, ED 0.02 or 0.05 = a + (bc/(k + c)), where k is the rumen outflow rate assumed to be either 2 or 5%/h describing 2 ruminal retention times (50 and 20 h, respectively). capability varies significantly among yeast strains, and it is affected by the VFA (Lee et al, 2003).…”
mentioning
confidence: 99%
“…Effective degradability, ED 0.02 or 0.05 = a + (bc/(k + c)), where k is the rumen outflow rate assumed to be either 2 or 5%/h describing 2 ruminal retention times (50 and 20 h, respectively). capability varies significantly among yeast strains, and it is affected by the VFA (Lee et al, 2003).…”
mentioning
confidence: 99%
“…Issatchenkia orientalis (syn. Candida krusei , Pichia kudriavzevii ) was experimentally used as probiotic in feed to promote animal health (Lee et al ., ; Koh & Suh, ) or as a candidate for bioethanol production (Kitagawa et al ., ). However, the anamorph form of I .…”
Section: Discussionmentioning
confidence: 99%
“…Issatchenkia orientalis (syn. Candida krusei, Pichia kudriavzevii) was experimentally used as probiotic in feed to promote animal health (Lee et al, 2003;Koh & Suh, 2009) or as a candidate for bioethanol production (Kitagawa et al, 2010). However, the anamorph form of I. orientalis, C. krusei, is reported as a notable pathogen especially for immune-compromised patients (Samaranayake & Samaranayake, 1994) and as a causative agent of mycotic mastitis in cattle (Watts, 1988;Elad et al, 1995;Sheena & Sigler, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Also, a paper published by Tamaki et al [27] showed that there is a glutathione-related detoxification system in the yeast I. orientalis where it can degrade S-(2-nitrophenyl) glutathione and S-(2-nitrophenyl) cysteine without suppressing its cell growth. Many researchers demonstrated that this yeast can rapidly degrade a series of volatile fatty acids, including acetic, propionic, butyric, and lactic acid [28][29][30][31].…”
Section: Isolates Used For Biodetoxificationmentioning
confidence: 99%